(untitled) (Research, Society and Development, 2022)
This work aims to present the teaching conceptions of the final years of Elementary School of Science Teaching, in two schools in the rural area of the municipality of Cametá-PA, in the light of BNCC. To obtain the data, bibliographic research (Marconi; Lakatos, 2010) on the object and semi-structured interviews (Manzini, 1990) were carried out with four Science teachers from the final years of Elementary School in the rural area of the municipality. To analyze the information, some notes from the Content Analysis were used (Bardin 2016). Among the data, we emphasize the difficulties mentioned by the teachers regarding the established by the BNCC and the lack of investments in continuing education that dialogue about this document and other legislation of the Basic School. In its entirety, it is considered a “general discontent” of the Science teachers participating in the research in relation to the BNCC.